Psychosocial, demographic, and clinical predictors of postpartum depression among mothers: a cross-sectional study - Sukesi, Niken; Saputri, Oktavia Ramadhani; Iswanti, Dwi Indah; Seman, Nordianna; Retnaningsih, Dwi; Nugraha, Rozaq I (Pediomaternal Nursing Journal, 2026)
Introduction: Postpartum depression (PPD) is a major public health issue with lasting effects on maternal well-being and child development. However, limited empirical evidence exists on the psychosocial, demographic, and clinical determinants of PPD among urban populations in Southeast Asia. This study aimed to identify psychosocial, demographic, and clinical predictors of postpartum depression among mothers residing in Semarang, Indonesia.Methods: A cross-sectional study was conducted among 168 postpartum women aged ≥17 years who had delivered a live infant and provided informed consent. Data were collected using validated tools, including the Edinburgh Postnatal Depression Scale (EPDS) to assess depressive symptoms. Independent variables included maternal age, education, employment, parity, mode and place of delivery, medical history, obstetric complications, socioeconomic status, anxiety level, and perceived spousal and family support. Chi-square tests and binary logistic regression were used to determine significant predictors.Results: The prevalence of mothers at risk of PPD was 50%. Logistic regression analysis showed that low education (OR = 7.18; 95% CI: 1.05–48.96; P-value = .044), moderate anxiety (OR = 5.52; 95% CI: 1.14–26.74; P-value = .034), limited spousal support (OR = .34; 95% CI: 0.15–0.80; P-value = .013), and lack of family support (OR = 6.15; 95% CI: 1.93–19.62; P-value = .002) were significant predictors of PPD.Conclusion: Psychosocial factors, particularly anxiety and insufficient social support, are key predictors of postpartum depression. Routine psychosocial screening and strengthened family-centered interventions are essential to reduce the risk and long-term impact of PPD.Keywords: depression postpartum; edinburgh postpartum depression scale; risk factors